Occurrence and distribution of persistent organic pollutants in the liver and muscle of Atlantic blue sharks: Relevance and health risks - Muñoz-Arnanz, Juan; Bartalini, Alice; Alves, Luis; Lemos, Marco F.L.; Novais, Sara C.; Jiménez, Begoña (Environmental Pollution, 2022)
Blue shark score among the most abundant, widely distributed and worldwide consumed elasmobranchs. In this work contents of PCBs, PCDD/Fs and PBDEs were studied by means of GC-HRMS in muscle and liver of sixty blue sharks from the North East Atlantic sampled in 2019. Concentrations relatively similar were found for PCBs and PCDD/Fs in comparison with those in Atlantic specimens from the same area sampled in 2015. In contrast, PBDE loads doubled, likely mirroring the increased environmental presence of these pollutants. This, together with the different congener profiles reported for the same species in other geographical areas, highlighted the blue shark's potential as bioindicator of the degree and fingerprints of regional pollution by POPs. Interesting dissimilarities between muscle and liver concentrations were detected, most likely ascribed to distinct toxicokinetics involved for the different pollutants. Whereas most POPs preferentially accumulated in liver, some did the opposite in muscle. BDE-209 was the most prominent example, being almost negligible its presence in liver (0.3%) while accounting for ca. 14% of the total PBDE content in muscle. Different findings in this regard described for other shark species call for focused research to ascertain the role of the species in this apparent favored metabolization of BDE-209 in the liver. From a consumption perspective, the concentrations found in muscle -the most relevant part in the human diet-for PCBs and dioxin-like POPs were below the EU maximum allowed levels in foodstuff. Conversely, in liver about 58% and 78% of samples overpassed the European levels for tolerable intake of i-PCBs and dioxin POPs, respectively. Concentrations of PBDEs exceeded EQS (0.0085 ng/g w.w.) established by the European Water Framework Directive in 100% and 92% of liver and muscle samples, respectively, which adds to the open debate of such as a reduce value for this current EQS. The authors thank María Ros, Bel´en Ruiz, Estela Nogales, Santiago Virseda, Pablo Poza and ...